Wykonaj redukcję wyrazów podobnych, a następnie oblicz wartość liczbową wyrażenia algebraicznego dla x = -5, y=3 i z=-1. a
a) 7x + 3y + 6x + 2
b) 8 + 4z + 6x + 10z
c) 7x + 3y + 8x + 9y
d) -5x + 3y -3z + 10
e) 6x^2 + 9z + 5x^2 - 8y
f) 5z^3 + 4z^2 + 3z - 25z - 10z^2 - 5z^3

2

Odpowiedzi

2010-02-08T15:56:09+01:00
A)
7x + 3y + 6x + 2
13x+3y+2

x = -5, y=3 i z=-1
13*(-5)+3*3+2=-65+9+2=-54

b)
8 + 4z + 6x + 10z
8+14z+6x

x = -5, y=3 i z=-1
8+14*(-1)+6*(-5)=8-14-30=-36

c)
7x + 3y + 8x + 9y
15x+12y

x = -5, y=3 i z=-1
15*(-5)+12*3=-75+36=-39

d)
-5x + 3y -3z + 10

x = -5, y=3 i z=-1
-5*(-5)+3*3-3*(-1)+10=25+9+3+10=47


e)
6x²+ 9z + 5x²- 8y
11x²+9z-8y

x = -5, y=3 i z=-1
11(-5)²+9*(-1)-8*3=11*25-9+24=275-24-9=242




f)
5z³+ 4z²+ 3z - 25z - 10z²- 5z³
-6z²-22z

x = -5, y=3 i z=-1
-6(-1)²-22(-1)²=-6*1-22*1=-6+22=16
2010-02-08T16:11:54+01:00
Dla : x = -5, y=3 i z=-1

a) 7x + 3y + 6x + 2=
7x + 6x +3y + 2 = 10x + 3y + 2
10x + 3y +2= 10 * (-5) + 3 * 3 + 2= -50 + 9 + 2 =-39

b) 8 + 4z + 6x + 10z=
6x + 4z + 10z + 8= 6x + 14z + 8
6x + 14z + 8= 6 * (-5) + 14 * (-1) + 8= -30 -14 + 8 = -36

c) 7x + 3y + 8x + 9y =
7x + 8x + 3y + 9y= 15x + 12y
15x + 12y = 15 * (-5) + 12 * 3 = -75 +36= - 39

d) -5x + 3y -3z + 10=
-5 * (-5) + 3 * 3 -3 * (-1) + 10 = 25 + 9 + 3 +10= 47

e) 6x² + 9z + 5x² - 8y =
6x² + 5x² - 8y + 9z = 11x² - 8y + 9z
11x² - 8y + 9z= 11 * (-5)² - 8 * 3 + 9 * (-1) = 11 * 25 - 24 -9= 275 - 24 - 9= 242

f) 5z³ + 4z² + 3z - 25z - 10z² - 5z³ =
3z - 25z + 4z² - 10z² + 5z³ - 5z³= -22z - 6z²
- 22z - 6z² = -22 * (-1) -6 * (-1)²= -22 -6 * 1 = -22 -6 = -28